Term Ḍaiq dalam al-Qur’an dan Relevansinya terhadap Kesehatan Mental Spiritual Di Era Digital - Jannah, Miftahul; Syefriyeni; Lukman Nul Hakim; Muh Mawangir; Kusnadi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This study aims to analyze the conceptual meaning of ḍaiq in the Qur'an through Toshihiko Izutsu's semantic analysis, as well as to articulate its relevance to spiritual and mental health in the digital age. The research method employed is qualitative-library, utilizing Toshihiko Izutsu's semantic approach to the Qur'an. The formal object of this study is the meaning of the term ḍaiq, while the material object is 12 verses containing the term. Data analysis was conducted in layers, including contextual studies, comparative meanings with juxtaposed meanings of ḍaiq, and historical research to reveal the worldview (weltanschauung) of the Qur'an. There is a shift in the worldview (weltanschauung) regarding the term ḍaiq in the Qur'an. Its meaning has evolved from physical-social pressure (Makkiyah-Madaniyah context) to a deeper psychological narrowness. The results of this study show that this psychological narrowness is relevant for analyzing phenomena in the digital age, especially Fear of Missing Out (FoMO), which is a modern manifestation of the condition of ḍaiq. This modern phenomenon of ḍaiq has a direct impact on spiritual and mental health, where feelings of isolation and anxiety hinder the attainment of peace of mind and the search for meaning in life.